Psychopharmacological adverse effects - Doyle, Louise; Keogh, Brian (My University, 2008)
Recent advances in the care of people with mental health problems have advocated for a move towards psychosocial based interventions and a reduction in the emphasis on medication based treatments. Despite this, psychopharmacology remains the main treatment for the majority of people in mental distress. The role of the mental health nurse in the administration of medications has become increasingly complex given the range of preparations available and their potential to induce adverse and toxic effects in susceptible individuals. Recognising adverse and toxic effects of psychopharmacology is a key part of the mental health nurse’s role and involves assisting individuals to manage side effects which may impact on the individuals’ quality of life. Occasionally medications used in contemporary psychiatry have the ability to induce potentially life threatening adverse reactions in a small number of individuals. Given the idiosyncratic nature of some of these effects and the difficulty in predicting people who are vulnerable, early recognition and intervention is imperative to a successful outcome should these occur. The purpose of this article is to provide mental health nurses with some guidance on the recognition and management of these potentially fatal adverse effects, namely agranulocytosis, neuroleptic malignant syndrome, serotonin syndrome and lithium toxicity.
PUBLISHED
Keywords: agranulocytosis, neuroleptic malignant syndrome, serotonin syndrome and lithium toxicity.; agranulocytosis, neuroleptic malignant syndrome, serotonin syndrome and lithium toxicity.